Double DVCS amplitudes including kinematic twist-3 and 4 corrections - Martinez-Fernandez, Victor; Pire, Bernard; Sznajder, Paweł; Wagner, Jakub (Pos : proceedings of science, 2024)
Generalized parton distributions (GPDs) are off-forward matrix elements of quark and gluon operators that work as a window to the total angular momentum of partons and their transverse imaging (nucleon tomography). To access GPDs one needs to look into exclusive processes which are usually studied in a kinematic regime known as the Björken limit. In this limit, the photon virtualities are much larger than the hadron mass M, and the kick to the hadron measured by the Mandelstam's variable t. It turns out that this is not enough for the purposes of a precise GPD extraction and, in particular, of nucleon tomography for which measurements in a sizable range of t are required. Deviation with respect to the Björken limit induces kinematic higher-twist corrections which enter the amplitudes with powers of $|t|/Q^2$ and $M^2/Q^2$, where $Q^2$ denotes the scale of the process (basically, the sum of photon virtualities in the case of DDVCS). There are also corrections by the name of "genuine" higher twists which are a separate topic and are not the subject of this research study.In this manuscript, we present novel calculations of DDVCS amplitudes off a (pseudo-)scalar target including up to kinematic twist-4 corrections. These results are important for measuring DDVCS, DVCS and TCS through the Sullivan process and off helium-4 target at the future Electron-Ion Collider (EIC) and JLab experiments. Preliminary numerical estimates for the pion target are provided.